COMPARATIVE ANALYSIS OF MINIMALLY INVASIVE TREATMENT METHODS FOR PROSTATIC ADENOMA - Abdurashidov Axrorjon Axmatjon oʻgʻli (Western European Studies, 2025)
Prostatic adenoma, also called benign prostatic hyperplasia, is a widespread urological condition among older men. Minimally invasive treatment methods have significantly improved its management by offering safer alternatives to traditional surgery with quicker recovery. This study reviews modern minimally invasive options such as transurethral resection of the prostate, holmium laser enucleation, prostatic artery embolization, water vapor thermal therapy, and radiofrequency ablation. Based on recent clinical studies since 2020, these methods are compared in terms of effectiveness, safety, patient suitability, and long-term results. While transurethral resection remains the standard, newer techniques like holmium laser enucleation and artery embolization offer similar benefits with fewer complications. Choosing the best method depends on individual patient characteristics, prostate size, symptom intensity, and overall health
Keywords: prostatic adenoma; benign prostatic hyperplasia; minimally invasive therapy